2012
DOI: 10.1159/000336619
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensins: Multifunctional Modulators of Infection, Inflammation and More?

Abstract: Defensins comprise one of the largest groups of host defence peptides, present throughout evolution, in fungi and flowering plants as well as in invertebrates and vertebrates. These cysteine-rich, cationic peptides have a common ability to kill a broad range of microorganisms including bacteria, yeast and viruses. As such, they are a strong component of the arsenal that is an organism’s innate immunity. It is becoming increasingly clear, however, that antimicrobial action is only one of the numerous roles of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
249
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(254 citation statements)
references
References 196 publications
(129 reference statements)
3
249
0
2
Order By: Relevance
“…All other transcript types were recovered in lower levels and typically with only one or two isoforms. It is noteworthy that the ancestral activity of these two peptide types is antimicrobial (72,73)-an activity which is retained by at least some isoforms expressed in the venoms of highly toxic frontfanged snakes. Another ancestrally recruited protein type, L-amino oxidase, also has well-documented anti-microbial activity (74).…”
Section: Discussionmentioning
confidence: 99%
“…All other transcript types were recovered in lower levels and typically with only one or two isoforms. It is noteworthy that the ancestral activity of these two peptide types is antimicrobial (72,73)-an activity which is retained by at least some isoforms expressed in the venoms of highly toxic frontfanged snakes. Another ancestrally recruited protein type, L-amino oxidase, also has well-documented anti-microbial activity (74).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the immunomodulatory function of HDPs may include manipulation of monocyte responses and APCs at multiple points of intervention as shown for LL-37 (21,23,24). Likewise, b-defensins have been shown to bind to cell-surface receptors and modulate the immune response (25). Inspired by the discovered immunoregulatory activities of HDPs, new synthetic immune defense regulators have been designed that selectively boost parts of the immune response (26,27) and are of therapeutic potential.…”
mentioning
confidence: 99%
“…In addition to the primarily recognized antimicrobial activities, hBD3 also functions as immune modulators linking innate and adaptive immunity (4,5). Analysis of intestinal resections obtained from infants with severe NEC revealed that low defensin mRNA and protein expression (6).…”
mentioning
confidence: 99%